Exploring cuproptosis as a mechanism and potential intervention target in cardiovascular diseases - Yang, Yang; Feng, Qi; Luan, Ying; Liu, Hui; Jiao, Yuxue; Hao, Huijie; Yu, Bo; Luan, Yi; Ren, Kaidi (Frontiers in Pharmacology, 2023)
Copper (Cu) is a vital trace element for maintaining human health. Current evidence suggests that genes responsible for regulating copper influx and detoxification help preserve its homeostasis. Adequate Cu levels sustain normal cardiac and blood vessel activity by maintaining mitochondrial function. Cuproptosis, unlike other forms of cell death, is characterized by alterations in mitochondrial enzymes. Therapeutics targeting cuproptosis in cardiovascular diseases (CVDs) mainly include copper chelators, inhibitors of copper chaperone proteins, and copper ionophores. In this review, we expound on the primary mechanisms, critical proteins, and signaling pathways involved in cuproptosis, along with its impact on CVDs and the role it plays in different types of cells. Additionally, we explored the influence of key regulatory proteins and signaling pathways associated with cuproptosis on CVDs and determined whether intervening in copper metabolism and cuproptosis can enhance the outcomes of CVDs. The insights from this review provide a fresh perspective on the pathogenesis of CVDs and new targets for intervention in these diseases.